Rural entrepreneurship and the context: navigating contextual barriers through women's groups. Issue 2 (9th November 2021) - Semkunde, Mohamed A.; Elly, Tumsifu; Charles, Goodluck; Gaddefors, Johan; Chiwona-Karltun, Linley
Abstract : Purpose: This study aims to examine how women's groups help women to navigate context-related barriers to their engagement in rural entrepreneurship. The paper combines the contextualisation of entrepreneurship framework and the feminist separatist theory to describe how women's groups in patriarchal rural communities enable women to circumvent context-related barriers and actively engage in rural entrepreneurship. Design/methodology/approach: Based on a case study of 12 women's groups engaged in paddy farming, rice processing and marketing in rural Tanzania, this study draws on semi-structured interviews with 46 women, four focus group discussions, four in-depth key informant interviews and non-participant observation. Findings: Rural women face unique context-related challenges that hinder them from effectively participating in rural entrepreneurship. Specifically, limited access to farmlands and profitable markets, lack of business networks, limited time, poverty and insufficient financial resources constrain women's engagement in entrepreneurship. To overcome these contextual barriers, rural women have organised themselves into groups to gain access to business services, business-related training, grants and business networks. Research limitations/implications: This study contributes to the existing literature on contextualising entrepreneurship by focussing on how rural contexts may constrain women's entrepreneurial engagement while showing how women respond to contextual barriers that enable them to participate in rural entrepreneurship. Practical implications: This study shows that women with low education can pursue rural entrepreneurship if they are supported through training and access to networks. This will support the performance of these groups of women. Originality/value: This study offers new insights into the role of women's groups in navigating gender-related constraints that hinder women from participating in rural entrepreneurship within the patriarchal context of low-income countries. Thus, new perceptions for the gender and rural entrepreneurship theory and the policy implications thereof are proffered.